PUBLIC AWARENESS OF ACUTE LEUKEMIA IN A SAMPLE OF IRAQI PEOPLE - Shams Mahdi; Moamar Shakir Mahmood; Shather Salah Mahdi; Shaddan Salah Mahdi (Global Journal of Public Health Medicine)
Introduction: Acute leukemia is a rapidly progressing hematologic malignancy that requires timely diagnosis and treatment. Public awareness and knowledge of acute leukemia, including its risk factors, symptoms, and treatment options, are critical for early detection and improved outcomes, and research in this area is limited in Baghdad, Al-Rusafa. This study aimed to assess the public’s awareness and knowledge of acute leukemia, including an understanding of its risk factors, symptoms, and role of treatment, prognosis, preventive measures, and metastasis. Methods: A cross-sectional survey was conducted among 1000 individuals in Baghdad, Al-Rusafa. A structured questionnaire collected data on participants' demographics, awareness, and knowledge of acute leukemia. Descriptive statistics and inferential analyses were performed to assess the level of awareness. Results: A total of 1000 participants completed the survey. The main participants were females. The majority of females and males were of non-university level education. The local community was the main source of participants’ knowledge. Environmental factors were the major risk factors reported by the participants. The majority of participants believed in the poor prognosis for acute leukemia (AL), but also the majority believed in the significant role of treatment. Poor knowledge was found regarding preventive measures and metastasis. Conclusion: The study reveals a substantial gap in public awareness and understanding of acute leukemia, its risk factors, symptoms, prognosis, treatment, prevention, and metastasis. These findings underscore the need for targeted public health education initiatives to improve awareness, ultimately promoting early detection and outcomes would be better for individuals at risk of acute leukemia.